Coverage and factors associated with influenza vaccination among kindergarten children 2-7 years old in a low-income city of north-western China (2014-2016) - Xu, Lili; Qin, Ying; Yang, Juan; Han, Wei; Lei, Youju; Feng, Huaxiang; Zhu, Xiaoyun; Li, Yanming; Yu, Hongjie; Feng, Luzhao; Shi, Yan (PloS one, 2017)
Influenza vaccination has been shown to be the most effective preventive measure to reduce influenza virus infection and its related morbidity and mortality. Young children aged 6-59 months are recommended as one of the priority groups for seasonal influenza vaccination in China. Our study was conducted to evaluate the level of influenza vaccination coverage during 2014-15 and 2015-16 influenza seasons among kindergarten children aged 2-7 years in Xining, a low-income city of north-western China, and to explore potential factors for noncompliance associated with influenza vaccination. The coverage rate of influenza vaccination was 12.2% (95 CI: 10.6-14.2%) in 2014-15 and 12.8% (95 CI: 11.1-14.7%) in 2015-16. The low coverage rate was found to be primarily associated with the lack of knowledge about influenza vaccine in children's parents. The most common reason for vaccine declination was the concern about adverse reactions of vaccine. Therefore tailored information should be provided by clinician and public health doctors for targeted groups through effective methods to improve public understanding of vaccination.